2003 Conference on Computer Vision and Pattern Recognition Workshop 2003
DOI: 10.1109/cvprw.2003.10008
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological Fragment Reconstruction Using Curve-Matching

Abstract: We present a novel approach to the problem of puzzle solving as it relates to archaeological fragment reconstruction. We begin with a set of broken fragments. In the first stage, we compare every pair of fragments and use partial curve matching to find similar portions of their respective boundaries. Partial curve matching is typically a very difficult problem because the specification of the partial curves are highly unconstrained and curve matching is computationally expensive. To address the first problem, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…Most objects fragment in a way that forms triple junctions, such as T-joints. McBride and Kimia (2003) reported that in samples of broken ceramic tiles, T-joints ranged from 70-89% of the junctions, while other triple junctions ranged from 6-9%, and non-triple junctions ranged from 5-20%. Figure 1 shows a Tjoint.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most objects fragment in a way that forms triple junctions, such as T-joints. McBride and Kimia (2003) reported that in samples of broken ceramic tiles, T-joints ranged from 70-89% of the junctions, while other triple junctions ranged from 6-9%, and non-triple junctions ranged from 5-20%. Figure 1 shows a Tjoint.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics concern orientation of pieces, whether there are missing pieces, whether the exterior boundary is known beforehand (such as a rectangular grid), whether there is a unique solution, and what types of junctions between pieces are allowed (Kleber, 2009). Some approaches consider image features of the pieces, such as color and texture (Nielsen, Drewsen, & Hansen, 2008) and others consider shape of pieces (Da Gama Leitao & Stolfi, 2002;Freeman & Garder, 1964;Goldberg, Malon, & Bern, 2002;Horst & Beichl, 1996;Krebs et al, 1997;Kong & Kimia, 2001;Lee et al, 2003;McBride & Kimia, 2003;Radack & Badler, 1982;Stringfellow et al, 2008;Zhu, Zhou & Hu, 2008), while (Weiss-Cohen & Halevi, 2005;Yao & Shao, 2003) consider both.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method can be extended to 3D fragments scanned by a laser range nder, where a pair of ridges are matched using a generalization of the 2D curve-matching approach. In [70], the rather high computational complexity of curve matching is reduced by adopting a multiscale technique. Papaioannou et al addressed the problem of 3D object reconstruction by just using the surface geometry of fragments, without assuming anything about the nal model to be reconstructed [80].…”
Section: Related Approachesmentioning
confidence: 99%